The relationship between theileria parva parva and t.p. lawrencei as shown by sporozoite antigen and ribosomal RNA gene sequences - Collins, Nicola, Elaine (My University, 1997)
The aim of this thesis was to develop DNA probes to distinguish between the protozoan parasites Theileria parva parva and T. p. lawrencei which cause East Coast fever (ECF) and Corridor disease respectively. ECF was eradicated from South Arrlca in 1954, and today Corridor disease has become the most important form of theileriosis. Although ECF has been eradicated, the vector ticks are still prevalent in South Africa and the cattle population would be highly susceptible to a recurrence of the disease, At present there is no reliable means of distinguishing between T.p. parva and T. p. lawrencei. Sequence differences between T. parva and other Theileria species have previously been found in the small subunit ribosomal RNA (rRNA) gene; probes designed to detect these sequence differences Can be used to distinguish between Theileria species. We therefore decided to search for differences in the rRNA genes of T. p. parva and T.p. lawrencei. To this end, the entire "RNA transcription unit was amplified from a cloned T. p, lawrence; parasite; the unit comprises the small subunit rRNA (SSUrRNA) gene, the internal transcribed spacer (ITS) and the large subunit rRNA (LSUrRNA) gene. The amplification products were cloned and sequenced, and the T.p, lawrencei rRNA sequence was compared to that of T. p, parva, While there was little variation in their SSUrRNA and LSUrRNA gene sequences, there was major sequence variation in the ITS The ITSs from twelve T. parva isolates were amplified, cloned and sequenced, and eleven characterisation oligonucleotide probes were identified. The T. p, parva isolates screened in this study hybridised with a limited subset of the probes, While the T. p. lawrencei isolates, hybridised with many more of the probes, indicating that the T. parva population in cattle is more homogenous than that in buffalo. There thus appears to have been a selection in cattle of a relatively homogenous subpopuiation of T. parva from a much larger, more diverse gene pool in buffalo. Although most T.p. parva isolates (93.5%) were detected by probe TPPI, and most T.p, lawrencei isolates (81.8%) were detected by
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy.
Keywords: Theileria parva -- South Africa.; Theileriosis.